2020
DOI: 10.1038/s41405-020-00045-2
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of preclinical and clinical dental students to altered smile aesthetics

Abstract: Introduction This prospective cohort study was designed to identify which components of a smile make it more or less aesthetically acceptable to dental students. Aim To investigate whether students at different stages of their undergraduate dental education held similar views on smile aesthetics. Additionally, to see whether students from the same ethnicity were more likely to have similar perceptions of smile aesthetics than students from different backgrounds. Methodology Dental students in either Year 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In similar study clinical students ranked a midline diastema to be significantly lower than preclinical students who perceived the smile with retroclined incisors as significantly less pleasing than the clinical students. Together with midline diastema, open bite was perceived as an unfavorable feature by both year-groups [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In similar study clinical students ranked a midline diastema to be significantly lower than preclinical students who perceived the smile with retroclined incisors as significantly less pleasing than the clinical students. Together with midline diastema, open bite was perceived as an unfavorable feature by both year-groups [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…While [ 29 ] reported that two-thirds of dental students thought the asymmetry of 2 mm was normal, Alhammadi et al [ 17 ] reported that dental students thought the asymmetry of 4.21 ± 1.13 mm was normal. At the same time, it was considered acceptable, according to [ 37 , 38 ]. In contrast, 91.0% of students did not find the midline shift attractive [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to those described in [ 10 , 41 ], verifying the impact of structures adjacent to the smile on the perception of upper dental midline deviations in 1 mm. On the other hand, [ 38 , 39 ] studied midline inclinations in an asymmetrical nose and chin and found them to influence perception. Silva and colleagues [ 42 ] observed that laypeople preferred canting of the dental midline in the same direction as the deviation of the nose and chin rather than the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…From 4th to 6th year, students attend more dental courses and clinical practicals; hence they are more critical to small deviations from an ideal smile. Many studies were conducted to investigate the students’ perceptions of altered smile esthetics ( 13 - 15 ) but these studies comprised only symmetric situations. The results obtained in our study show that we should have a very good communication with patients to avoid “overtreating” them if they have gingival asymmetry of 2 mm or less.…”
Section: Discussionmentioning
confidence: 99%